Sustainable Agriculture Model Development to Control Agricultural Land Conversion in Kemiren Tourism Village, Banyuwangi Regency - Parmawati, Rita; Yanti, Indah; Hakim, Luchman; Kamira Gunawan, Fahdynia; Oktaviantina Rahmawati, Nadhea; Muhammad, Fadhil (Jurnal Penelitian Pendidikan IPA, 2023)
The conversion of agricultural land in Kemiren Tourism Village has the potential to affect the environment, socioeconomic, and cultural of the surrounding community. To address the issue of land conversion in Kemiren Tourism Village, this study aims to develop a sustainable agriculture model. The development of this dynamic system involves several stages: determining system objectives, conducting a needs analysis, formulating problems, and identifying the system. The analysis suggests an increase in agricultural land conversion from 2020 to 2030, with the potential to convert all agricultural land into non-agricultural land, particularly for tourism purposes. The reduction of agricultural land in Kemiren Tourism Village leads to a decline in both the community’s rice production and food security. However, the growing demand for rice due to land being optimized for tourism increases rice production. To address this issue, this study recommends a scenario that includes strengthening the agricultural ecosystem and bolstering the socio-economic conditions of the population, leading to a reduction rate of agricultural land conversion by 25% until 2030.